(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
This study investigates carbon nanotube textiles as advanced personal protection equipment for firefighters and first responders. Carbon nanotubes are lightweight, flame resistant, and possess high mechanical and thermal properties. Carbon nanotubes are also thermally anisotropic, meaning they easily conduct heat along the axis of an individual tube, and are relatively insulating across the tube's diameter. By recognizing this anisotropic behavior, heat transfer through a layer of aligned carbon nanotubes in a garment can be partially redirected to a cold reservoir thereby protecting the wearer from heat stress and exhaustion. Finite element models were developed to simulate a carbon nanotube layer embedded in a firefighting garment and thermally connected to a cold reservoir. Simulation showed that under heat stress conditions, firefighter skin temperature was considerably reduced by the cooling layer.